Evaluation of the use and efficacy of (neo)adjuvant chemotherapy in angiosarcoma: a multicentre study. Issue 4 (26th August 2020) - Constantinidou, Anastasia; Sauve, Nicolas; Stacchiotti, Silvia; Blay, Jean-Yves; Vincenzi, Bruno; Grignani, Giovanni; Rutkowski, Piotr; Guida, Michele; Hindi, Nadia; Klein, Alexander; Thibaud, Valentin; Sufliarsky, Jozef; et al.
Abstract : Introduction: Angiosarcomas constitute approximately 2% to 3% of all soft tissue sarcomas, are characterised by an aggressive clinical behaviour and poor outcome. Optimal management of localised angiosarcomas consists of complete surgical resection with or without radiation. However, due to the infiltrating nature of this disease, complete resection is often not possible. Despite optimal management, the outcome of patients with localised disease remains poor. The role of (neo)adjuvant chemotherapy in angiosarcomas remains undefined. The aim of this study is to document the outcome of patients treated with (neo)adjuvant chemotherapy and assess the feasibility of performing a prospective trial by evaluating the number of patients treated at sarcoma referral centres. Methods: A retrospective search within participating EORTC (European Organisation for Research and Treatment of Cancer) sites for patients treated with (neo)adjuvant chemotherapy was made. Patients treated between January 2007 and January 2016 were included. Results: A total of 15 institutions participated and 86 patients were evaluable, 43 were treated with neoadjuvant, 27 with adjuvant chemotherapy and 16 with both. At the time of analysis, the median follow-up from diagnosis was 4.6 years. Median overall survival (OS) was 4.9 years (2.9 N) and the percentage alive at 4 years was 57.9 (45.5 to 68.4). The median disease-free survival was 1.4 years (0.9 to 1.7) and the percentage disease-free at 4 years was 26.8% (17.9 to 36.5). Conclusion: The outcome of angiosarcoma patients treated with (neo)adjuvant chemotherapy in this case series compares favourably with previously published data. Due to the aggressive nature of angiosarcoma, a prospective trial of neoadjuvant chemotherapy should be considered.